MEMORI KETAKUTAN ANAK SEBAGAI SUMBER INSPIRASI KARYA SENI PATUNG - Sukmawati, silviya; Indratmo, effy (Sanggitarupa, 2021)
ABSTRACTViolence from parents and violence from the immediate environment at the age of children causes them to become children who are easily afraid of sounds (Verbal), fear of physical violence (objects), and fear of the immediate environment. This final artwork project aims to create a sculpture art with the theme of the memory of a child's fear, which also explains the concept and process of creation and also the visual aesthetics of sculpture. The shape of the memory of children's fear is portrayed in the media of sculpture art with cast printing techniques. The creation of sculpture in this final project provides more insight into empirical experiences in creating works of art as well as the deepening of concepts in children's memory of fears.Keywords: Memory, Fear, Children, Sculpture Art, Cast Printing.  ABSTRAKKekerasan dari orangtua dan kekerasan dari lingkungan terdekat pada usia anak-anak menyebabkan diri menjadi anak yang mudah takut akan suara (verbal), takut akan kekerasan Fisik (benda), dan takut akan lingkungan terdekat. Tujuan dari karya seni patung tugas akhir ini adalah menciptakan karya seni patung yang mengambil tema Memori ketakutan Anak yang juga menjelaskan konsep dan proses penciptaan serta estetika visual karya seni patung. Wujud memori ketakutan anak dituangkan kedalam media karya seni patung dengan teknik cetak Cor. Penciptaan karya seni patung tugas akhir ini memberikan wawasan yang lebih dari pengalaman empiris dalam penciptaan karya seni serta pendalaman konsep dalam memori ketakutan anak.Kata Kunci: Memori, Ketakutan, Anak, Seni Patung, Cetak Cor.